The Effect of Variable Ratios of Na2O/K2O Oxides in Glazes Containing BaO, ZnO, and ZrO2: Structural Analysis, Characteristic Temperatures, and Surface Properties - Janusz Partyka; Dawid Kozień; Katarzyna Pasiut (Applied Sciences)
In this paper, the glazes of a multicomponent system (SiO2-Al2O3-CaO-MgO-Na2O-K2O-BaO-ZnO-ZrO2) were examined. This work focuses on five glazes and the difference between them as the molar ratio of the alkali oxides Na2O/K2O. Analysis of fired glazes focused on changes in phase composition (qualitative and quantitative) microstructure performed during observations made by scanning electron microscopy (SEM). The changing molar ratios were also studied in the structure analysis based on the result of data obtained by middle infrared (MIR) and Raman spectroscopy. The characteristic temperatures of the analyzed glazes were also designated using high-stage microscopy. Surface properties such as the color and roughness of the fired glazes were measured by means of a spectrometer and confocal microscopy as well. The amount and type of crystalline phases with the molar ratio of alkali oxides in the analyzed glazes were changed. In the glazes, the crystalline phase of a solid solution of plagioclase was obtained. The results obtained indicate that glazes with a predominant potassium oxide are characterized by lower characteristic temperatures and greater surface smoothness. Structure analysis indicates a different role for the five-molar ratio of Na2O/K2O.